The effect of management commitment, safety rules and procedure and safety promotion policies on nurses safety performance: the moderating role of consideration of future safety consequences - Mashi, Munir Shehu; Subramaniam, Chandrakantan; Johari, Johanim (Medwell Journals, 2017)
This study suggests that Consideration of Future Safety Consequences (CFSC) would moderate the relationship between safety promotion policies, management commitment and safety rules and procedures on nurse’s safety performance.Using Social Exchange Theory (SET) and Construal Level Theory (CLT), data was obtained among 229 nurses from Abuja secondary health facilities, Nigeria. Results from partial least squares analysis shows that management commitment positively relates to safety compliance and safety participation and safety promotion policies positively relates to safety participation.Conversely, the relationship between safety promotion policies and safety compliance was not established in this study. Likewise the relationship between safety rules and both safety compliance and participation were not supported. Additionally, CFSC moderates the relationships between safety rules and procedures and nurses safety participation.This study offers empirical evidence in the support of CFSC as a moderator.This contributes to the utility of SET and CLT.Further more, to optimally enhance safe hospitals environment, management should give nurse’s safety high priority and provide incentives for safety to the nurses and pay closer attention to nurses CFSC in developing an intervention on how increase nurses safety behavior.